Delivery of an at-home transcranial direct current stimulation intervention to mitigate pain in patients with end-stage kidney disease receiving hemodialysis (ESKD/HD) - Van Zyl, Jordan; Knotkova, Helena; Kim, Patricia; Henderson, Charles R.; Portenoy, Russell K.; Berman, Nathaniel; Frederic, Melissa W.; Reid, M. Carrington (Frontiers in Pain Research, 2023)
Background: Poorly controlled pain remains a problem for many patients with end-stage kidney disease requiring hemodialysis (ESKD/HD) and customary approaches to pain management (e.g., opioids, non-steroidals) confer substantial risk. Accordingly, non-pharmacologic therapies are needed for use in this population. Non-invasive transcranial Direct Current Simulation (tDCS) constitutes a promising nonpharmacologic method for pain management in affected individuals. Aims: This study seeks to: 1) determine the effects of an 8-week course of at-home tDCS versus sham tDCS on pain intensity, pain interference, medication usage, quality of life, and mood; 2) determine if tDCS effects vary by race/ethnicity; and 3) ascertain patient satisfaction with device use. Methods: This double-blind, randomized, sham-controlled clinical trial will enroll 100 ESKD/HD patients with moderate-to-severe (≥4 on 0-10 scale) chronic pain. The active study intervention consists of 20 minutes of tDCS delivered over the primary motor cortex 5 days/week for 8 weeks. The comparator is a sham procedure that provides no effective stimulation. The primary outcome analysis will evaluate efficacy of tDCS for pain reduction after two months of stimulation. We will also assess the effects of treatment on analgesic consumption, pain interference, depressed mood, and quality of life. The statistical plan will include fixed classification factors for treatment (versus sham), clinic sites, and assessment time, and the interaction of these factors adjusting for covariates (e.g., race/ethnicity, pain level). Conclusion: At-home tDCS constitutes a promising nonpharmacologic treatment for pain mitigation in persons with ESKD/HD. This unique RCT could transform the way pain is managed in this vulnerable population.